Presupposition And Entailment In The Film â€œBeauty And The Beastâ€ By Stephen Chbosky And Evan Spilotopoulos - Laudry, Andrew Fraditya; Farhan, Muhammad; Rahmah, Robyatul; Damanik, Emiliya Sukma Dara (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2022)
ABSTARCTThis study aims to analyze presupposition and entailment found in the film â€œBeauty And The Beastâ€ By Stephen Chbosky and Evan Spilotopoulos. The method that used in this study is descriptive qualitative research, which attempt identify and analyze based on theory of George Yule about the types of presupposition, the meaning of presupposition in the film â€œBeauty And The Beastâ€. According to Yule 1996, there are 6 types of presupposition, they are : Existensial presupposition, Factive presupposition, Lexical presupposition, Structural presupposition, Non-factive presupposition, and Counterfaction presupposition. The data was taken from the source of data, which is from script of beauty and the beast by stephen chbosky and evan spilotopoulos. The result of this study is the authors found that there are 2 Existensial presupposition, 2 Factive presupposition, 2 Lexical presupposition, 6 Structural presupposition, 2 Non-factive presupposition and authors didnâ€™t find dialogue about Counterfactive presupposition and The Entailment. The dominant types of presupposition that authors found in script of beauty and the beastâ€™s film is structural presupposition.KEYWORDS : Entailment, Film, Pragmatic, Presupposition